Pengenalan Pengolahan Sampah Popok menjadi Media Tanaman Hias dalam Pemberdayaan Masyarakat untuk Pengelolaan Limbah Rumah Tangga - Rachmawan Budiarto; Novi Astuti Indra Paranita; Rias Janathun Qolbi; Ridha Hanifah; Lintang Ratri Handaru Putri; Salsabila Khulukin Hasanah; Adrian Yoga Permana; Tri Rahayu Kusumaningsih; Endang Sulastri; Sujono (Direktorat Pengabdian kepada Masyarakat, 2023)
Disposable baby diaper waste causes water and soil pollution when disposed in rivers, drains, streets, ground, and other places. This condition is triggered by the lack of awareness of disposable baby diaper waste management by the community, especially youngmothers who have toddlers. An appropriate solution is needed to overcome this problem and reduce the negative impact on the environment. This activity aims to introduce a waste management approach and determine the impact of the introduction of the approach in overcoming the waste problem at Tanjungrejo Village river, Madiun District, Madiun Regency, East Java Province. The research applied a qualitative method with observation and interview approach. The research sample was selected by using a purposive sampling method. Based on observations, each mother mostly threw two or three disposable baby diapers used by toddlers at landfills. Many mothers still do not know how to reduce the growing amount of disposable baby diaper waste. Media posters,presentation slides, and demonstrations of the process of making pots and ornamental plant media were carried out in the implementation of the socialization on July 2023 at the Tanjungrejo Village Head Office. Through this socialization, all mothers who have been interviewed express interest in trying and practicing the process of disposable baby diaper waste into pots and ornamental plant media. Therefore, this socialization activity can be a breakthrough innovation in the form of utilizing disposable babydiaper waste into pots and ornamental plant media.